Features of effective professional learning: a case study of the implementation of a system-based professional learning model. Issue 1 (1st January 2016) - Labone, Elizabeth; Long, Janette
Abstract : The impact of quality teaching on student learning has led to an increased focus on professional learning to support and improve teacher practice. Review of the literature on effective professional learning suggests six elements that support sustained change in teacher practice; namely, focus, learning components, feedback, collaborative practices, temporal elements and coherence. While these practices have been drawn from reviews of studies of effective professional learning, there has been little attempt to validate the effectiveness of collective implementation of these elements in broad-based professional learning. To address this, this study assesses the validity of these elements in a system-based professional learning programme implemented in Diocesan schools in Australia. The paper first discusses the key practices for effective professional learning within these six elements, and then reports on case studies of three Catholic schools that have implemented the system-based professional learning programme. The research maps the implementation strategies of these three schools against the key practices in the six elements. The findings support the importance of the presence of all six elements in effective implementation but also suggest that the principal's commitment to professional learning is a pivotal factor in sustaining changed practices.